2012
DOI: 10.1083/jcb.201201153
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian GW220/TNGW1 is essential for the formation of GW/P bodies containing miRISC

Abstract: Localization of the miRNA-induced silencing complex to GW/P bodies by GW220/TNGW1 may regulate the fate of target mRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Anti-GW220 antibody only detects a subset of the P-bodies containing TNRC6 family proteins ( Fig. 5B, control KD), consistent with the observation that not all P-bodies contain GW220 protein (Castilla-Llorente et al 2012). It was striking that P-bodies (with and without GW220) were barely detected when Pan3S was depleted ( Fig.…”
Section: Pan3l and Pan3s Have Different Roles In Relation To P-bodiessupporting
confidence: 85%
See 1 more Smart Citation
“…Anti-GW220 antibody only detects a subset of the P-bodies containing TNRC6 family proteins ( Fig. 5B, control KD), consistent with the observation that not all P-bodies contain GW220 protein (Castilla-Llorente et al 2012). It was striking that P-bodies (with and without GW220) were barely detected when Pan3S was depleted ( Fig.…”
Section: Pan3l and Pan3s Have Different Roles In Relation To P-bodiessupporting
confidence: 85%
“…Thus, it is possible that when the functions of the two human Pan3 isoforms in mRNA deadenylation and decay (see below) are disrupted, it may compromise proper cytoplasmic mRNP remodeling as manifested by changes in P-body dynamics and constituents. Indeed, a recent study using human U2OS cells identified a distinct subclass of P-bodies (GW/P-bodies) containing a unique GW protein splice variant GW220 (Castilla-Llorente et al 2012). This raised an interesting question as to whether the individual Pan3 isoforms have distinct roles in GW/P-body formation.…”
Section: Pan3l and Pan3s Have Different Roles In Relation To P-bodiesmentioning
confidence: 99%
“…4b). We infer that this may reflect the recruitment of ectopic and endogenous Ago proteins into aggregates 30 , whose loading potential and stability control might be altered. We therefore concentrated our further studies on endogenous mAgo2.…”
Section: Resultsmentioning
confidence: 98%
“…Based on the RPF reductions attributable to these two repression modes, their relative contributions to repression are then calculated (Figure S2). Of the two modes, mRNA degradation dominates in U2OS cells (Figure 1B), despite the presence of a P-body subtype reported to impart increased translational repression (Castilla-Llorente et al, 2012). …”
Section: Resultsmentioning
confidence: 99%